2020
DOI: 10.1111/jcpe.13298
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CBCT image quality on the confidence of furcation measurements

Abstract: Background To investigate the impact of scanning parameter in cone‐beam computed tomography (CBCT) images on accuracy and confidence with measurements of furcation involvement (FI) in maxillary molars. Material and methods Six half cadaver heads with present maxillary molars (n = 10) were available. CBCT scans with the fixed‐parameter field of view (4 × 4 cm, 12 × 17 cm) amperage and voltage (4 mA, 90 kV) and with varying scan modes (SM), that is images/scan (IS), voxel sizes (VZ) and rotation (R), were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Compared with intrasurgical measurements of furcation defects, HD-CBCT and LD-CBCT showed moderate Cohen’s kappa values. This is in line with the findings of other studies testing different CBCT protocols for furcation diagnostics 13 . These moderate Cohen’s kappa values may be explained by limitations of the clinical probe used to measure the fine furcation defects.…”
Section: Discussionsupporting
confidence: 93%
“…Compared with intrasurgical measurements of furcation defects, HD-CBCT and LD-CBCT showed moderate Cohen’s kappa values. This is in line with the findings of other studies testing different CBCT protocols for furcation diagnostics 13 . These moderate Cohen’s kappa values may be explained by limitations of the clinical probe used to measure the fine furcation defects.…”
Section: Discussionsupporting
confidence: 93%
“…Another critical issue to be highlighted is that different CBCT settings and devices may influence image accuracy for FI detection 21,31,32 , and a small field of view should be preferred 28 . In summary, clinical, CBCT and intra-surgical measurements showed similar results in assessing maxillary molar furcation involvement.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was concluded previously that in some cases, direct clinical measurements and IRs do not provide sufficient information on the morphology of intrabony periodontal defects, therefore surgical planning cannot be carried out properly [10,11]. Application of CBCT scans has proven to be beneficial in the diagnostics of periodontal defects [15][16][17][18][19][20][21][22]; however, it should be used in cases where conventional methods are unable to provide an exact diagnosis [26]. In the present study, in five out of six cases conventional diagnostic methods did not provide sufficient information on defect characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The application of cone-beam computed tomography (CBCT) in periodontal diagnostics has been proposed by many authors [12][13][14]. A series of in vitro and in vivo studies have demonstrated that CBCT is superior to IRs in the detection of certain periodontal defects (i.e., furcation defects, three wall intrabony defects, midbuccal intrabony defects, or dehiscence-type defects) [15][16][17][18][19][20][21][22]; however, it is difficult to justify the cost-benefit ratio of the higher irradiation dose [23][24][25]. Therefore, CBCT should only be used for periodontal diagnosis if conventional radiographic methods do not provide a sufficient amount of information [26].…”
mentioning
confidence: 99%
See 1 more Smart Citation